Penggunaan Model Problem-Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Kelas V SD - Siska Mardaleni; Nur Azmi Alwi (Universitas Pahlawan Tuanku Tambusai, 2023)
This study was inspired by field data that do not conform to ideal conditions, so there is still little impact on student learning outcomes. In general, this study aims to describe how integrated thematic learning in grade V SD using the Problem Based Learning (PBL) model improved student learning outcomes. Classroom action research, also known as CAR, employs both qualitative and quantitative methods. The study was carried out during the second semester of the academic year 2022–2023. The outcomes showed that in arranging cycle I acquired a normal of 87.45% then expanded in cycle II to 97.2%, execution of learning on the educator viewpoint, cycle I got a normal of 82.1% and encountered an expansion in cycle II to 92.8% and on the understudy perspective, cycle I got a typical score of 82.1% then expanded in cycle II to 92.8%, understudy learning results in cycle I got a typical score of 76.81 then expanded in cycle II to 89.73 . The Problem-Based Learning (PBL) model has the potential to enhance student learning outcomes in class V SD thematic learning